Thrombosis and severe acute respiratory syndrome coronavirus 2 vaccines: vaccine-induced immune thrombotic thrombocytopenia - Young Shil Park (The Korean Pediatric Society, 2021)
The development of vaccines against severe acute respiratory syndrome coronavirus 2, which features high mortality and morbidity rates, has progressed at an unprecedented rate, and vaccines are currently in use worldwide. Thrombotic events after vaccination are accompanied by thrombocytopenia, and this issue was recently termed vaccine-induced immune thrombotic thrombocytopenia. This manuscript describes recently published guidelines and other related issues and demonstrates characteristic cases.